Correlation between inflation member power and anthropometric characteristics on side jumper performance in field football golfers - Segundo, Rodolfo Machado de Souza (2017)
The present study aimed to investigate the correlation between lower limb power and anthropometric characteristics goalkeepers in the base of the Hunter Athletic Club. The sample was 8 goalkeepers football field, under - 18, with a mean age of 16 years. We evaluated height, full statue, wingspan, % fat, and lower limb power in tests of horizontal and vertical thrust. For the correlation of the data, we used the test of Pearson Multiple Correlation with significance level of p <0.05. The main results were presented by full height correlation r = 0.70 (p <0.009) and vertical jump r = 0.73 (p <0.006), followed by horizontal impulse r = 0.65 (p <0.01) and scale r = 0.66 (p <0.01). Suggesting that improving the rates of overall height, wingspan, standing long jump and vertical jump, improving the probability of defense of the goalkeeper in a lateral projection. Being aspects of genetic potential mainly on the height and the ability to work in the evolution of muscle power, the determining factors for a good performance.